The intestinal ecosystem and probiotics - Altomare, Roberta; Damiano, Giuseppe; Gioviale, Maria Concetta; Palumbo, Vincenzo Davide; Maione, Carla; Spinelli, Gabriele; Sinagra, Emanuele; Abruzzo, Alida; Lo Monte, Giulia; Tomasello, Giovanni; Lo Monte, Attilio Ignazio (Progress in Nutrition, 2016)
The term “probiotic” comes from the Greek “pro bios” and means “pro-life”. Nowadays, an increasing number of pharmaceutical preparations and functional foods are enriched with probiotics and for the patients it is increasingly important to receive the information needed to know how to orient in the choice. The benefits from probiotics are many and include the modulation of the intestinal microflora (stimulation of beneficial bacteria and inhibition of pathogens), the support of bowel function and the stimulation of the immune system. This broad spectrum of beneficial effects contributes to maintain efficient the intestinal ecosystem. Therefore, probiotics are an useful tool to prevent the formation of disorders and/or pathologies. The aim of this review is to describe the intestinal ecosystem and how probiotics could be effective in the treatment and prevention of possible alterations.